Total intravenous anaesthesia in ponies using detomidine, ketamine and guaiphenesin: Pharmacokinetics, cardiopulmonary and endocrine effects - Taylor, P. M.; Luna, Stélio Pacca Loureiro [UNESP]; Sear, J. W.; Wheeler, M. J. (Elsevier, 1995)
Pharmacokinetics and some pharmacological effects of anaesthesia induced by a combination of detomidine, ketamine and guaiphenesin were investigated in eight ponies. Cardiopulmonary function was studied and plasma met-enkephalin, dynorphin, β-endorphin; arginine vasopressin, adrenocorticotrophin, cortisol, 11-deoxycortisol and catecholamine concentrations were measured. The combination produced slight cardiorespiratory depression, hyperglycaemia and a reduction in haematocrit. There were no changes in plasma opioids, pituitary peptides or catecholamines. Plasma cortisol concentration decreased and plasma 11-deoxycortisol increased indicating a suppression of steroidogenesis. Steady state ketamine and guaiphenesin concentrations were attained during the infusion period, and ketamine concentrations likely to provide adequate analgesia for surgical operations were achieved (more than 2.2 μg ml-1). Steady state detomidine concentration was not attained. The ponies took on average 68 minutes to recover to standing and the recovery was uneventful.
Keywords: anesthetic agent; argipressin; catecholamine; corticotropin; cortodoxone; detomidine; dynorphin; guaifenesin; hydrocortisone; ketamine; metenkephalin; anesthesia; cardiopulmonary insufficiency; catecholamine blood level; hematocrit; hormone blood level; hormone release; horse; hyperglycemia; intravenous drug administration; nonhuman; standing; steroidogenesis; Anesthesia, Intravenous; Anesthetics; Anesthetics, Dissociative; Animal; Drug Interactions; Endocrine Glands; Guaiacol Glyceryl Ether; Hemodynamics; Horses; Hypnotics and Sedatives; Imidazoles; Ketamine; Male; Respiration; Support, Non-U.S. Gov't; Equus caballus